Recent Advances in Cytology-A Review - R.Hariharan1 , N.Anitha2 , E.Rajesh2 , N.AravindhaBabu3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In olden days, specificity and sensitivity of oral cytology is poor. Utilizing traditional oral cytology for theconclusive diagnosis of malignancyand premalignant lesions. But with the recent cytological techniquespaves cytology to conclude a final diagnosis. This reestablished interest is somewhat because of thepresentation of a specific brush that gathers a full-thickness epithelial sample and not simply sloughed cells,just as examination of that sample with computer support and analysis. There is an assortment of adjunctivestrategies have been acquainted with possibly upgrade the finding of the cytologic examples including DNAexamination, immunocytochemistry, molecular analysis, and liquid based preparations. An expansion insensitivity (>96%) and specificity (>90%) of the oral brush biopsy with computer support, diagnosis hasbeen accounted for detection of malignant and premalignant lesions. Brush cytology is significant to forestallmisdiagnosing suspicious oral lesions.